1984
DOI: 10.1128/iai.43.2.637-643.1984
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cross-reactive promastigote cell surface antigens of some leishmanial stocks by 125I labeling and immunoprecipitation

Abstract: Externally oriehted surface membrane constituents of promastigotes from several Leishmania species were radiolabeled with 125I. Autoradiographs of cell surface-labeled and sodium dodecyl sulfate-polyacrylamide gel electrophoresis-separated proteins of the stocks revealed distinctive patterns of bands in the molecular weight range of 6,000 to 240,000. Immunoprecipitation of detergent extracts of the labeled promastigote stocks with anti-Leishmania donovani membrane serum demonstrated that each of the stocks con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
3

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 14 publications
2
20
0
3
Order By: Relevance
“…Two L. donovani specific proteins, termed gp70-2 and dp72, were recognized in a direct dot-blot assay, with 90% and 100% sensitivity, and 984% and 93% specificity, respectively (Jaffe & Zalis 1988). In previous studies, a major surface glycoprotein, termed gp63, identified on several Leishmania species (Lepay, Nogueira & Cohn 1983, Gardiner, Jaffe & Dwyer 1984, Colomer-Gould et al 1985, Bouvier, Etges & Bordier 1987, Campbell, Kurath & Fleischman 1992, was found to elicit a strong humoral immune response during VL, CL and MCL infections (Lepay, Nogueira & Cohn 1983, Colomer-Gould et al 1985, Lemesre et al 1985, Reed, Badaro & Cheri-Lloyd 1987, Kutner et al 1991). It appears that the L. chagasi (and L. donovani) recombinant gp63 was also recognized by VL patient sera in a protein A-ELISA test (Reed et al 1990), with 84% sensitivity, and 100% specificity (Schreffler et al 1993).…”
Section: Infanrum Lem 497 Polypeptides Separated By 10% Polyacrylamentioning
confidence: 97%
See 1 more Smart Citation
“…Two L. donovani specific proteins, termed gp70-2 and dp72, were recognized in a direct dot-blot assay, with 90% and 100% sensitivity, and 984% and 93% specificity, respectively (Jaffe & Zalis 1988). In previous studies, a major surface glycoprotein, termed gp63, identified on several Leishmania species (Lepay, Nogueira & Cohn 1983, Gardiner, Jaffe & Dwyer 1984, Colomer-Gould et al 1985, Bouvier, Etges & Bordier 1987, Campbell, Kurath & Fleischman 1992, was found to elicit a strong humoral immune response during VL, CL and MCL infections (Lepay, Nogueira & Cohn 1983, Colomer-Gould et al 1985, Lemesre et al 1985, Reed, Badaro & Cheri-Lloyd 1987, Kutner et al 1991). It appears that the L. chagasi (and L. donovani) recombinant gp63 was also recognized by VL patient sera in a protein A-ELISA test (Reed et al 1990), with 84% sensitivity, and 100% specificity (Schreffler et al 1993).…”
Section: Infanrum Lem 497 Polypeptides Separated By 10% Polyacrylamentioning
confidence: 97%
“…The recognition of the Leishmania-94 kDa antigen by NW-VL sera was not as surprising as molecular studies do not distinguish L. chagasi and L, infantum, which probably should be regarded as the same species (Beverley, Ismach & McMahon-Pratt 1987). Cross-reactions among various species of Leishmania are well known (McMahon-Pratt & David 1981, Lepay, Nogueira & Cohn 1983, Gardiner, Jaffe & Dwyer 1984, Anthony et al 1985, Colomer-Gould et al 1985, Edges et al 1985, Bouvier, Etges & Bordier 1987, allowing crossreactivities among VL and CL sera. In particular, we previously showed (Rolland-Burger et al 1991) that the 94 kDa antigen was detected by 1 : 200 diluted VL sera in L. infantum and L. donovani species, but also in those causing CL (L. tropica, L. major, L. guyanensis, L. mexicana).…”
Section: Infanrum Lem 497 Polypeptides Separated By 10% Polyacrylamentioning
confidence: 99%
“…In addition, it has been reported recently (16) that mAb and rabbit sera raised against promastigotes of one Leishmania species recognized similar surface determinants in others.…”
mentioning
confidence: 94%
“…These studies compare in detail the external accessibility and expression of L. tropica promastigote and amastigote membrane molecules. Other reports have focused primarily on the promastigote stage of various Leishmania genera and have essentially confirmed the relatively complex nature of promastigote membranes (4,7,8,21). However, little information is available concerning the membrane constituents of amastigotes, the leishmanial form present in parasitized M+, and perhaps the more relevant stage to human disease.…”
Section: Discussionmentioning
confidence: 99%